Pengaruh Pendekatan PMRI Menggunakan Konteks Uang Rupiah dalam Menyelesaikan Soal Cerita Terhadap Kemampuan Numerasi Siswa Kelas V SD - Fadilla, Asiatul; Helsa, Yullys (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy skills are essential competencies in addressing the demands of the 21st century; therefore, learning should be designed contextually by guiding students from concrete experiences toward abstract understanding. This study aimed to analyze the effect of the Indonesian Realistic Mathematics Education (PMRI) approach using the context of rupiah currency in solving word problems on the numeracy skills of fifth-grade elementary school students. The method employed was a pre-experimental design with a one-group pretest-posttest format. The population consisted of all fifth-grade students at SD Negeri 13 Kapalo Koto, with a sample of 6 students selected through stratified purposeful sampling based on their mathematics summative scores. Data were collected using a numeracy skills test. Data analysis using the paired sample t-test revealed a significance value of 0.099 (> 0.05), indicating that statistically there was no significant effect of the PMRI approach on students’ numeracy skills. However, the effect size measured by Cohen’s d was 0.826, indicating a large practical effect. The N-Gain test result showed an average score of 0.2515, which falls into the low category, although variations in improvement were observed among students. These findings indicate that the implementation of PMRI has not shown a statistically significant effect, but it demonstrates potential practical contributions to improving students’ numeracy skills.